SUMBER BELAJAR DAN MEDIA PEMBELAJARAN DALAM PELAKSANAAN KURIKULUM 2013 DI SDN 1 PIDODOWETAN - Pamungkas, Dwi Anggara; Artharina, Filia Prima; Arisyanto, Prasena (JURNAL SINEKTIK, 2020)
The purpose of this research is to find out the utilization of learning resources and learning media in the implementation of the 2013 curriculum at SDN 1 Pidodowetan in Patebon Subdistrict, Kendal. This research uses a cauldron method. The data source in this research was obtained from principals, teachers, and students in grades I, II, IV and V of SDN 1 Pidodowetan. Data in the form of observations and interviews. The implementation of thematic learning in the 2013 curriculum at SDN 1 Pidodowetan has been running for two years. The use of learning resources and learning media is still not optimal. Teachers are based on teacher and student books and other reference books. Learning becomes less meaningful because teachers do not prepare creative learning tailored to student development. The learning process is still teacher-centered so that students are still the object of education. Students are more interested in learning by using learning media that makes students actively participate.